Majid Majidi and Baran: Iranian Cinematic Poetics and the Spiritual Poverty of Rumi - Pittman, Michael (The journal of religion and film, 2011)
Over the past several decades, Iranian Cinema, through the use of themes and stories, shots and pacing, has developed a narrative style outside of Western-dominated cinematic forms. The work of Iranian director Majid Majidi reflects some of the many themes of Sufi poetry. In particular, Jalāl al-Dīn Rūmī’s poetry characteristically and repeatedly expresses the beauty of the spiritual poverty that results in the struggle with the nafs, or the lower soul. Through the lens of the work of Rumi on spiritual poverty, this article shows how the themes and filmic techniques used by Majidi in the 2000 film Baran reveal a rich and compelling narrative of cinema.